Improving services for parents with intellectual disability and their families: Views of Canadian social service workers. (1st September 2022) - Pacheco, Laura; Aunos, Marjorie; Feldman, Maurice; McConnell, David
Abstract: How adults with intellectual disability fare in the parenting role depend, to varying degrees, on the adequacy of supports and services provided. The available research suggests that service providers are often ill‐equipped to accommodate their support needs. The purpose of this qualitative descriptive study was to explore the perspectives of Canadian social service workers on what is required to improve services and build systems capacity to more effectively support parents with intellectual disability, their children and families. A total of 39 workers, identified by parents with intellectual disability as their key workers, were interviewed. To build systems capacity to support these parents and families, and to address institutionalised discrimination, key workers highlighted the need for entry‐to‐practice and continuing professional education to develop worker capabilities for reflective practice, relationship‐building and research utilisation; accommodative caseload management, giving workers the time, flexibility and the professional supervision they need to deal with complexity and fashion individualised service responses; and, a common framework, with defined service pathways, to facilitate interagency case planning and, in turn, continuity in service provision. The question is not whether adults with intellectual disability can be effectively supported in the parenting role; the question is whether the political will exists to do what is necessary to ensure they are.